Dietary patterns, nutritional status, and mortality risks among the elderly - Liu, Zhen; Xu, Di; Xu, Wen-xiu; Fei, Yin-jiao; Wang, Dan-dan; Deng, Fei; Tang, Jin-hai (Frontiers in Nutrition, 2022)
Introduction While most epidemiological studies have focused on the effects of individual dietary patterns and nutritional status on health, the relationships between the combinations of these factors and patient prognosis requires further investigation. Objective This study explored mortality risk in individuals with different combinations of dietary patterns or nutritional status. Methods Unsupervised K-means clustering was used to classify populations. The analyses included Cox proportional risk and competing risk models. Results After considering a complex sampling design, the results showed that among 12,724 participants aged >60 years, 6.99% died from cancer and 10.47% from cardiovascular and cerebrovascular disease (CCVD). After correcting for participant baseline information and chronic conditions, the geriatric nutritional risk index and healthy eating index (HEI) were negatively associated with the risk of all-cause and cause-specific mortality. The opposite was true for the dietary inflammatory index (DII). After sorting the population three clusters based on study scores showed higher risks of all-cause mortality and cancer-related death in Cluster 2 and 3. Discussion These results suggest that different nutritional status and dietary patterns are associated with the risk of all-cause mortality and death from cancer and CCVD in people aged >60 years in the United States. Dietary patterns with high HEI and low DII were beneficial to health, whereas nutritional status needs to be maintained at a level that is not too low.